The Effect of Antenatal Vaginal Progesterone Administration on Uterine, Umbilical, and Fetal Middle Cerebral Artery Doppler Flow: A Cohort Study - Maged, Ahmed M.; Shoab, Amira Y.; Hussein, Eman A.; Alsawaf, Ahmed H.; Mahmoud, Doaa S.; AbdAllah, Ameer A.; Dahab, Sherif; Darwish, Mohamed; Ali, Yahia Z.; Badran, Haitham (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate the effect of vaginal progesterone (P) administration during the second and third trimesters of pregnancy on Doppler velocimetry of uterine, umbilical, and middle cerebral vessels.Study Design A prospective cohort study conducted on 80 women at risk for preterm labor. Uterine artery, umbilical artery, and middle cerebral artery (MCA) Doppler indices were measured before and after 1 week of administration of 200 mg twice daily vaginal P. The primary outcome parameter was the change of MCA pulsatility index (PI) after P administration. Secondary outcomes included changes in uterine artery and umbilical artery Doppler measurement.Results There was no significant changes of umbilical artery resistance index (RI) (0.69 ± 0.049 vs. 0.68 ± 0.041), umbilical artery PI (1.14 ± 0.118 vs. 1.11 ± 0.116), uterine artery RI (0.66 ± 0.12 vs. 0.66 ± 0.107), uterine artery PI (1.00 ± 0.26 vs. 1.016 ± 0.24), and MCA PI (1.27 ± 0.18 vs. 1.26 ± 0.23) measurements before and after 1 week of P administration, respectively.Conclusion Administration of vaginal P has no significant effects on uterine artery, umbilical artery, and MCA Doppler indices.
Keywords: progesterone; preterm birth; umbilical artery Doppler; uterine artery Doppler; middle cerebral artery Doppler